Interaction effect of adjacent small defects on the fatigue limit of a medium carbon steel. Issue 1 (28th July 2016) - Åman, M.; Okazaki, S.; Matsunaga, H.; Marquis, G.B.; Remes, H.
Abstract: Structural steels contain various material irregularities and natural defects which cause local stress concentrations from which fatigue cracks tend to initiate. Two defects in close proximity to each other may affect local stress distributions, and thus, begin to interact. In this paper, the effect of interacting small cracks on the fatigue limit is systematically investigated in a medium carbon steel. The growth of interacting cracks, as well as the characteristics of non‐propagating cracks and microstructural aspects, was closely examined via the plastic replica method. It was found that although the fatigue limit is essentially controlled by the mechanics of interacting cracks, based on their configuration, the local microstructure comprised ferrite and pearlite has a statistical scatter effect on the behaviour of interacting cracks and non‐propagating thresholds. With respect to the fatigue limit, when two defects were in close proximity, they behaved as a larger single defect. However, with greater spacing between defects, rather than mechanical factors, it is the local microstructure which determines the location and characteristics of non‐propagating cracks.